Genetic Risk Factors for Metabolic Dysfunction-Associated Steatotic Liver Disease - Yiying Pei; George Boon-Bee Goh (Gut and Liver)
Metabolic dysfunction-associated steatotic liver disease (MASLD), is the most common cause of liver disease, and its burden on health systems worldwide continues to rise at an alarming rate. MASLD is a complex disease in which the interactions between susceptible genes and the environment influence the disease phenotype and severity. Advances in human genetics over the past few decades have provided new opportunities to improve our understanding of the multiple pathways involved in the pathogenesis of MASLD. Notably, the PNPLA3, TM6SF2, GCKR, MBOAT7 and HSD17B13 single nucleotide polymorphisms have been demonstrated to be robustly associated with MASLD development and disease progression. These genetic variants play crucial roles in lipid droplet remodeling, secretion of hepatic very low-density lipoprotein and lipogenesis, and understanding the biology has brought new insights to this field. This review discusses the current body of knowledge regarding these genetic drivers and how they can lead to development of MASLD, the complex interplay with metabolic factors such as obesity, and how this information has translated clinically into the development of risk prediction models and possible treatment targets.